EARLY RESULTS OF LAPAROSCOPIC SURGERY FOR COLON CANCER AT CAN THO ONCOLOGY HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the early outcomes of laparoscopic surgery in the treatment of colon cancer.Materials and Methods: A descriptive study was conducted on 42 patients diagnosed with colon cancer who underwent laparoscopic colectomy with lymph node dissection at Can Tho Oncology Hospital from January 2023 to October 2024.Results: The mean age of the participants was 56.2 ± 12.6 years, with males accounting for 69%. The most common tumor location was the sigmoid colon (54.8%). The mean operative time was 158.5 ± 43.6 minutes, and the mean estimated blood loss was 59.4 ml. The average number of harvested lymph nodes was 16.6 ± 4.2. The overall complication rate was 21.4%, including surgical site infection (9.5%) and postoperative ileus (16.7%), no cases of anastomotic leakage or mortality were recorded. The mean postoperative hospital stay was 7.1 ± 0.8 days.Conclusion: Early outcomes of laparoscopic surgery for colon cancer treatment show that this is a safe and feasible method, with low complication rates  and a reliable maximum number of harvested lymph nodes..
Keywords: Laparoscopic surgery, colon cancer, Can Tho Oncology Hospital.